2014
DOI: 10.1177/1071100714559270
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Evaluation of Varying the Number of Loops in a Repair of a Physiological Model of Achilles Tendon Rupture

Abstract: We cannot recommend attempting more limited exposures with sutures in frayed tendon as this may lead to early repair failure. We provided a physiologic model utilizing frayed tendon ends that resembles in vivo Achilles tendon rupture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Since a larger incision of mean 4.2 cm was used in the delayed presentation to mobilise adherent separated tendon ends, the incision provided the opportunity to strengthen the core suture repair. Recent meta-analyses of biomechanical studies have shown comparable strength for the Krackow suture and Bunnell suture [30], however, to optimise the strength of the Krackow suture, the locking loops must be inserted beyond the frayed ends of the ruptured tendon [13] increasing incision length. Using this described technique once the adherent tendon ends have been mobilised, and the percutaneous modified Bunnell and Kessler core sutures inserted, the repair strength was also be augmented by a circumferential running [20] or locking suture [14] without increasing the incision length and increasing the associated risks.…”
Section: Discussionmentioning
confidence: 99%
“…Since a larger incision of mean 4.2 cm was used in the delayed presentation to mobilise adherent separated tendon ends, the incision provided the opportunity to strengthen the core suture repair. Recent meta-analyses of biomechanical studies have shown comparable strength for the Krackow suture and Bunnell suture [30], however, to optimise the strength of the Krackow suture, the locking loops must be inserted beyond the frayed ends of the ruptured tendon [13] increasing incision length. Using this described technique once the adherent tendon ends have been mobilised, and the percutaneous modified Bunnell and Kessler core sutures inserted, the repair strength was also be augmented by a circumferential running [20] or locking suture [14] without increasing the incision length and increasing the associated risks.…”
Section: Discussionmentioning
confidence: 99%
“…Most Achilles tendon rupture ends are horsetail-like avulsions, and the quality of the tendon tissue at the rupture site is poor. Grieco et al's [18] biomechanical studies have confirmed that in the Krackow technique, suture repairs incorporated into frayed tendon portions result in significantly greater gapping and lower maximal failure forces than repairs in unfrayed tendons do. Therefore, if the locking loop suture is performed on avulsed Achilles tendon tissue, early functional rehabilitation may lead to loose locking and tendon elongation.…”
Section: Discussionmentioning
confidence: 92%
“…All analyses were performed with the statistic software R (version 3.1.2, www.r-project.org) using the R-package lme4 for the linear mixed effects model. Based on the literature, we chose a sample size of N = 8 for each group [14,[30][31][32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%